2020
DOI: 10.1158/1538-7445.am2020-ct147
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT147: Phase 1 dose escalation of MSC-1, a humanized anti-LIF monoclonal antibody, in patients with advanced solid tumors

Abstract: Leukemia Inhibitory Factor (LIF) is a pleiotropic cytokine, which is highly expressed in a subset of tumors and correlates with poor prognosis. LIF is hypothesized to contribute to tumor microenvironment immunosuppression and regulation of cancer stem cells. MSC-1 is a first-in-class humanized IgG1 monoclonal antibody that potently and selectively inhibits LIF. In pre-clinical models, MSC-1 decreases tumor growth through inhibition of STAT3 signaling, promoting immune stimulatory macrophages and increasing tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…26 Recently, the results of a phase I study investigating the safety and efficacy of MSC-1, a first-in-class humanized IgG1 MAb that potently and selectively inhibits LIF, have been reported. 32 Eligible patients had advanced relapsed/refractory solid tumors and received treatment with MSC-1 intravenously (75 mg-1500 mg) once every 3 weeks as a single agent until disease progression. Single agent MSC-1 was well tolerated with no dose limiting toxicities observed during the first cycle of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recently, the results of a phase I study investigating the safety and efficacy of MSC-1, a first-in-class humanized IgG1 MAb that potently and selectively inhibits LIF, have been reported. 32 Eligible patients had advanced relapsed/refractory solid tumors and received treatment with MSC-1 intravenously (75 mg-1500 mg) once every 3 weeks as a single agent until disease progression. Single agent MSC-1 was well tolerated with no dose limiting toxicities observed during the first cycle of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-1, a humanized IgG1 mAb targeting LIF, is being evaluated in a phase I clinical trial as monotherapy in patients with advanced, refractory solid malignancies ( NCT03490669 ). Results available from 41 patients who received a median of 3 prior lines of therapy revealed a DCR of 22% with 9 patients achieving SD that lasted over 16 weeks [ 73 ]. In addition, tissue samples confirmed an increase in both M1:M2 ratio and cytotoxic CD8 + T cells.…”
Section: Inhibitory Targets Beyond Immune Checkpointsmentioning
confidence: 99%
“…Although no grading is specified, the most common AEs included fatigue (20%) and gastrointestinal symptoms (20%). There was one patient with HNSCC who developed grade 2 osteonecrosis of the jaw; however, he had previously received radiation therapy to the area and had been exposed to denosumab [ 73 ]. Unfortunately, this trial was terminated early due to safety concerns.…”
Section: Inhibitory Targets Beyond Immune Checkpointsmentioning
confidence: 99%
“…Overall, the study found that high levels of LIF were associated with decreased response to anti-PD1 therapies, and that LIF nAb when used in conjunction with anti-PD1 therapy could be a potential therapeutic option for patients with solid tumors exhibiting high LIF expression ( 82 ). In 2019, a humanized LIF nAb called MSC-1 entered phase 1A clinical trials and has been recommended to enter phase 2 dose trials for patients with relapsing or non-responsive solid-state tumors ( 83 ). Clearly, LIF and the LIFRβ have relevant connections to cancer growth and metastasis that warrant additional research and definition.…”
Section: Lif and Lifrβ Expression In Cancermentioning
confidence: 99%